PF.42 Unfused Amnion and Chorion (UAC) After 15 Weeks Gestation and Association with Chromosomal Abnormalities. (26th April 2013) - Raouf, S; Adcock, C; Hay, D; Ashworth, J
Abstract : Objectives: To assess a possible association between UAC and Trisomy 21. Method: Medical records of all women undergoing amniocentesis between April 2008 and October 2012 at RDH were analysed highlighting UAC and karyotype result. Results: 425 women underwent amniocentesis for standard screening rationale. 33 fetuses were diagnosed with trisomy 21, (incidence of 7.6%). 21 women had their amniocentesis delayed because of UAC (404 did not as the membranes were normally fused - NFM). Of these, 10 had a result confirming the presence of Trisomy 21, the remaining 11 had a normal result, 23 of the 404 with NFM had Trisomy 21. Conclusion: We suggest that NFM has a negative association with Trisomy 21 with high NPV and may be helpful in counselling. Furthermore UAC seems to be only associated with Trisomy 21 and no other chromosomal abnormality in this population. We suggest further prospective study of this phenomenon. Abnormalities of cell adhesion molecules (encoded on C21) are well described in Down's (DSCAM – Down's Cell Adhesion Molecule) and this suggests a possible aetiology.